A bactericidal calix[4]arene-based nanoconstruct with amplified NO photorelease. Issue 34 (20th July 2016) - Di Bari, Ivana; Picciotto, Roberta; Granata, Giuseppe; Blanco, Anna R.; Consoli, Grazia M. L.; Sortino, Salvatore
Abstract : Visible light excitation of a calix[4]arene-based nanoconstruct encapsulating a hydrophobic NO releaser triggers NO generation with high efficiency, resulting in a considerable antibacterial activity against both Gram positive and Gram negative bacteria strains. Abstract : A hydrophobic N -dodecyl-3-(trifluoromethyl)-4-nitrobenzenamine has been synthesized as a suitable NO photodonor and encapsulated in a nanocontainer based on a polycationic calix[4]arene derivative, leading to a supramolecular micellar-like nanoassembly ca . 45 nm in diameter. Visible light excitation of this nanoconstruct triggers NO generation with an efficiency remarkably higher than that observed for the free NO photoreleaser. This amplified NO release results in considerable antibacterial activity against Staphylococcus aureus (ATCC 6538) and Pseudomonas aeruginosa (ATCC 9027) as representative Gram positive and Gram negative bacteria, respectively.